Performance, genetic variations and interrelationships in different traits of sorghum (Sorghum bicolor L. Moench) genotypes - Mohammed, Mohammed; Ibrahim, Abu Elhassan; Elzein, Ibrahim (Gezira Journal of Agricultural Science; Vol 13 No 2 (2015), 2015)
Eighteen sorghum genotypes were evaluated over three consecutive seasons (2009,2010,and 2011) at three locations ( Rahad Research farm of the Agricultural Research Corporation (ARC), Sudan, Gedarif Research Station farm North Gedarif and South Gedarif region). Both experiments conducted in  North and South Gedarif were rainfed, while that conducted at Rahad station was irrigated. A randomized complete block design with four replicates was used .The objective was to estimate the general performance, genetic variability and interrelationships of grain yield and its components. Data were collected on days to 50% flowering, plant height, number of heads/m², head length (cm), head width (cm),1000 seed weight (g) and grain yield (kg/ha). The study found  that there were highly significant differences among genotypes in  all the characters studied  except head width in season 2011.The early maturing genotypes were Milo (59-64 days), Gesheish      (60-67 days) , AG-8 (59-65 days) and Butana (62-68 days), an indication that these genotypes would fit quite well in short rainy seasons of  North Gedarif environment. The late maturing genotypes were Tabat (68-83days),Wad Ahmed (69-83 days), Faki Mustahi (68-88 days) and Tetron (73-88 days) which were suitable to be grown under Rahad and South Gedarif environments . The highest grain yields (kg/ha) were exhibited by the genotypes Butana (735 kg/ha), Wad Ahmed (2572 kg/ha), and Mugod   (2545 kg/ha). Grain yield was positively   and highly significantly correlated with head width (0.65**)  and number of heads/m² (0.46**) .Accordingly, the simple linear correlation and path coefficient analysis indicated that head width and number of heads/m² could be used as potential selection criteria in breeding programs for developing high yielding sorghum genotypes.           تم تقييم ثمانية عشر سلالة من الذرة الرفيعة  لثلاثة مواسم متتالية (2009، 2010 و2011) في ثلاثة مواقع هي محطة بحوث الرهد ومحطة بحوث القضارف ،( شمال وجنوب القضارف)، هيئة البحوث الزراعية، السودان واللتان تمت فيهما الزراعة بالأمطار أما محطة بحوث الرهد بالري الأنسيابي. استخدم تصميم القطاعات العشوائية الكاملة بأربعة مكررات  وذلك لتقدير أداء انتاجية الحبوب، التباين الوراثي والعلاقة بين الصفات. تم قياس عدد الايام حتي 50% ازهار،  طول النبات ، عدد القناديل/متر² ، طول القندول ، عرض القندول ، وزن الالف حبة وانتاجية الحبوب. أظهرت النتائج وجود فروق معنوية عالية لمعظم الصفات التي درست ماعدا عرض القندول في موسم 2011م. السلالات المبكرة هي مايلو (59-64 يوم) ،قشيش (60–67 يوم) ، أرفع قدمك -8 (59–65 يوم) وبطانة (62–68 يوم). هذا يوضح ان هذه السلالات يمكن زراعتها في المناطق قليلة الامطار وهي تناسب بيئة شمال القضارف. الاصناف المتأخرة هي طابت (68- 88 يوم)، ود أحمد(69-83 يوم) ، فكي مستحي(68-88 يوم) ، وتترون(73-88 يوم) حيث يمكن زراعتها في بيئات مثل الرهد وجنوب القضارف. السلالات ذات الانتاجية العالية هي بطانة (735 كجم /هكتار) ، ود أحمد (2572 كجم/ هكتار) ومقد (2545 كجم /هكتار). ارتبط انتاج الحبوب ايجابياً ومعنوياً مع عرض القندول (** 0.65) وعدد القناديل/ متر² (** 0.46) ، وعليه أوضح معامل تحليل المسار أن عرض القندول وعدد القناديل/ متر² يمكن استخدامها كصفات انتخاب في برامج التربية لتطوير سلالات من الذرة  الرفيعة عالية الانتاجية.